The Genus Koilodepas Hassk. (Euphorbiaceae) in Malesia (Biodiversitas Journal of Biological Diversity, 2016)
The Malesian genus Koilodepas Hassk. has been revised based on the morphological and anatomical character using available herbarium collection in Herbarium Bogoriense and loan specimens from Kew Herbarium and Leiden Rijksherbarium. The present study is based on the observation of 176 specimens. Eight species has been recognized, namely K. bantamense, K. cordifolium, K. frutescns, K. homalifolium, K. laevigatum, K. longifolium, K. pectinatum, and two varieties within K. brevipes. The highest number of species is found in Borneo (5 species), three of them are found endemically in Borneo, K. cordisepalum endemically in Aceh, and K. homalifolium endemically in Papua New Guinea. A phylogenetic analysis of the genus, with Cephalomappa as outgroup, show that the species within the genus Koilodepas isin one group, starting with K. brevipes as a primitive one and K. bantamense occupies in an advance position.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeyword: Koilodepas Hassk., Malesia, outgroup, phylogenetic analysis, outgroup